2008
DOI: 10.1111/j.1745-7254.2008.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine as a regulator of internal ribosome entry site

Abstract: Aim: Studies of eukaryotes have yielded 2 translation initiation mechanisms: a classical cap-dependent mechanism and a cap-independent mechanism proceeding through the internal ribosomal entry site (IRES). We hypothesized that it might be possible to identify compounds that may distinguish between cap-dependent translation and cap-independent IRES-mediated translation. Methods: To facilitate compound screening, we developed bicistronic reporter constructs containing a β-galactosidase gene (β-gal) and a secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…We noted that the effects of dsRNA are similar to that of EMT by reducing the coupling constant between the canonical and noncanonical pathways. To confirm whether the noncanonical pathway was coupled to NF- κ B/RelA through an IRES dependent mechanism, we perturbed an IRES mediated translation using amantadine, a known inhibitor of IRES-dependent translation [46]. A549 cells were activated using poly I:C treatment in the absence or presence of amantadine, and canonical and noncanonical pathway kinetics were measured.…”
Section: Resultsmentioning
confidence: 99%
“…We noted that the effects of dsRNA are similar to that of EMT by reducing the coupling constant between the canonical and noncanonical pathways. To confirm whether the noncanonical pathway was coupled to NF- κ B/RelA through an IRES dependent mechanism, we perturbed an IRES mediated translation using amantadine, a known inhibitor of IRES-dependent translation [46]. A549 cells were activated using poly I:C treatment in the absence or presence of amantadine, and canonical and noncanonical pathway kinetics were measured.…”
Section: Resultsmentioning
confidence: 99%
“…The relative luciferase activity in RAN 5= UTR reporter-transfected cells was significantly increased compared with that observed in vector-transfected cells (Fig. 6D), and this IRES activity was specifically inhibited by amantadine, an IRES inhibitor (29,30) (Fig. 6E).…”
Section: Ran Is Necessary and Sufficient For Ev71 Replicationmentioning
confidence: 86%
“…Therefore, the amantadine and ribavirin could be applied to patients infected with ECV 5. It was reported that the amantadine could suppress the IRES mediated translation, and ribavirin is a nucleoside analogue with broad-spectrum antiviral activity by decreasing viral replication in EV71 [23,24]. …”
Section: Discussionmentioning
confidence: 99%